2022
DOI: 10.1111/1365-2656.13661
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the interaction between age‐specific predation and chronic disease in the Greater Yellowstone Ecosystem

Abstract: Predators may create healthier prey populations by selectively removing diseased individuals. Predators typically prefer some ages of prey over others, which may, or may not, align with those prey ages that are most likely to be diseased. The interaction of age‐specific infection and predation has not been previously explored and likely has sizable effects on disease dynamics. We hypothesize that predator cleansing effects will be greater when the disease and predation occur in the same prey age groups. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Determining the relationship between predation and disease prevalence in prey species has the potential to inform monitoring and management of both predators and prey. For example, monitoring of the ratio of adult to juvenile predator mortality could be indicative of disease burdens in the population (Brandell et al, n.d.). An increase in predation rates of adults likely indicates a change in their vulnerability, potentially due to disease.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Determining the relationship between predation and disease prevalence in prey species has the potential to inform monitoring and management of both predators and prey. For example, monitoring of the ratio of adult to juvenile predator mortality could be indicative of disease burdens in the population (Brandell et al, n.d.). An increase in predation rates of adults likely indicates a change in their vulnerability, potentially due to disease.…”
Section: Figurementioning
confidence: 99%
“…The GYE has a diverse predator population, is well studied providing empirical parameters for the model, and had CWD emerge in 2018 (Krumm et al, 2010; Miller et al, 2008; Smith et al, 2020). In this system, the novel model was used to determine the effect of predation by wolves and cougars on CWD prevalence in elk and deer given variation in both disease prevalence and predation with age (Brandell et al, n.d.). Unsurprisingly, the model indicated that predator cleansing effects were greatest when predators selected upon the age class with the most infections.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations